To solve the system of equations given:
- \( y = 3x - 2 \)
- \( y = -x - 6 \)
We can set the two expressions for \( y \) equal to each other since they are both equal to \( y \):
\[ 3x - 2 = -x - 6 \]
Now, let's solve for \( x \):
-
Add \( x \) to both sides: \[ 3x + x - 2 = -6 \] \[ 4x - 2 = -6 \]
-
Add 2 to both sides: \[ 4x = -6 + 2 \] \[ 4x = -4 \]
-
Divide both sides by 4: \[ x = -1 \]
Now that we have \( x = -1 \), we can substitute this value back into either of the original equations to find \( y \). We'll use the first equation:
\[ y = 3(-1) - 2 \] \[ y = -3 - 2 \] \[ y = -5 \]
So the solution to the system of equations is:
(-1, -5)
This matches the first option provided in your responses.